Teleworking in the context of the COVID-19 pandemic - Malița, Daria-Ștefania (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
The COVID-19 pandemic has brought with it a phenomenon that had not been experienced before, namely social distancing. With the restrictions imposed by the authorities regarding free movement, a large part of companies and public institutions have had to quickly rethink their operational models and turn to telework. Thus, teleworking has become widespread and has become a safeguard tool for both employees and employers. In this article, I aim to analyze a series of aspects regarding teleworking, its regulation, the differences between teleworking and working from home, the rights and obligations of the parties, the support measures for employees and employers, the advantages and disadvantages of remote work, but also the practical trends in other states about the application of telework.

Pandemia COVID-19 przyniosła ze sobą niespotykane wcześniej zjawisko, jakim jest dystans społeczny. Wobec ograniczeń nałożonych przez władze w zakresie swobodnego przemieszczania się, duża część firm i instytucji publicznych musiała szybko przemyśleć swoje modele działania i przejść do telepracy. W ten sposób telepraca stała się powszechna i stała się narzędziem ochronnym zarówno dla pracowników, jak i pracodawców. W tym artykule przean alizowano szereg aspektów dotyczących telepracy, jej regulacji, różnic między telepracą a pracą w domu, praw i obowiązków stron, środków wsparcia dla pracowników i pracodawców, zalet i wad pracy zdalnej, ale także praktyczne trendy w innych państwach dotyczące stosowania telepracy.
Telepraca w kontekście pandemii COVID-19
An earlier version of this paper was presented at the Conference of Students, Masters and Doctoral Students in Law, Sibiu, Romania. The paper Support measures for employees and employers regarding teleworking in the context of the COVID-19 pandemic was published in the Conference of Students, Masters and Doctoral Students in Law Journal (ISBN: 978-606-39-0890-3), p. 256–263.
Keywords: teleworking; employees; employers; COVID-19; telepraca; pracownicy; pracodawcy